PENGARUH INDEPENDENSI, KARIR DAN PENJENJANGAN, OBJEKTIVITAS, DAN PENGALAMAN AUDIT TERHADAP EFEKTIVITAS AUDIT INTERNAL - Nurhaliza Nurhaliza; Yuneita Anisma; Devi Safitri (AKUNTABILITAS, 2021)
This study aims to find out the effects of independent, careers and grading, objectivity, and audit experience on the effectiveness of internal audits. This research uses purposive sampling method. The data in this research comes from a questionnaire from 52 respondents. The processing of the data in this research applies Structural Equation Model based on Partial Least Square  with the help of SmartPLS 3. According to the research findings, independence and audit experience significantly affect the effectiveness of internal audits. While careers and grading and objectivity do not significantly affect the effectiveness of internal audits.